2021
DOI: 10.3390/nu13113964
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of Malnutrition and Loss of Muscle Strength after COVID-19: A Major and Neglected Component of Long COVID-19

Abstract: Post-acute consequences of COVID-19, also termed long COVID, include signs and symptoms persisting for more than 12 weeks with prolonged multisystem involvement; most often, however, malnutrition is ignored. Method: The objective was to analyze persistent symptoms, nutritional status, the evolution of muscle strength and performance status (PS) at 6 months post-discharge in a cohort of COVID-19 survivors. Results: Of 549 consecutive patients hospitalized for COVID-19 between 1 March and 29 April 2020, 23.7% di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 34 publications
1
45
0
6
Order By: Relevance
“…Concerning weight changes, the majority of our population was overweight before the COVID-19 pandemic started. This is consistent with previous data [ 4 ] showing a high rate of people with obesity being infected and placed in intensive care, and that might explain why patients did not reach their pre-hospitalization weight after rehabilitation. Indeed, nutritional recommendations systematically provided to the patients aimed to help them normalize their BMI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Concerning weight changes, the majority of our population was overweight before the COVID-19 pandemic started. This is consistent with previous data [ 4 ] showing a high rate of people with obesity being infected and placed in intensive care, and that might explain why patients did not reach their pre-hospitalization weight after rehabilitation. Indeed, nutritional recommendations systematically provided to the patients aimed to help them normalize their BMI.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we observed that sarcopenia—defined as reduced muscle mass and strength—was related to the duration of hospitalization after COVID-19 infection [ 21 ], and a common hypothesis is that hospitalization and/or a SARS-CoV2-related increase in muscle weakness likely causes, in turn, a decrease in the GIR [ 22 , 23 ]. From this perspective, pre-existing comorbidities are also likely involved since they are associated not only with the need for hospitalization but also likely with persistent alteration [ 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Gerard et al followed 288 COVID-19 patients discharged from the hospital at 30 days post-discharge and six months post-discharge to evaluate the presence of malnutrition. At 30 days, 47.2% of patients evaluated were malnourished, and at 6 months, 36% of the patients previously identified with malnutrition still had malnutrition based on GLIM criteria [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the hypothesis that these patients obviously do not receive optimal nutritional care. Additionally, disease symptoms and de-arrangement of the nutritional status persists until 6 months after hospital discharge, as an interesting French study published in this SI informed us [ 6 ]. The authors supported the hypothesis that COVID-19 patients had a much higher risk of developing muscle weakness, malnutrition and functional loss.…”
mentioning
confidence: 94%